If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 * 4x = 0 Multiply -1 * 4 9x + -4x = 0 Combine like terms: 9x + -4x = 5x 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| -4x-4(x-1)=-32-4 | | 12+2p=3(4-5p) | | 2b-4-6b-6= | | 2.4h+1=7 | | -10n+3(8+8n)=-6(n+4) | | 75=42-3x | | 2(x-2)+3x=-6-8 | | 16=.432h-10.44 | | 16=.432-10.44 | | -3(5n-4)+3n= | | 2x+10-4x-5= | | -2.2x-3.35=6.25+x | | 4L-3=25 | | 15x-20=-3x+16 | | 4+c= | | 4xc= | | (x+4)(x+3)=18 | | 3x+4x=10 | | 4-3x=3.5 | | 10(x+5)=3(x+33) | | 4-3x=-15 | | 3(x-5)=57-5x | | 1000+600+6x=750+400+9x | | 2x-8=96-11x | | 15-y=13 | | 6-6k-2k= | | 2*(x+3)=8 | | 0=x^2+4x-3 | | 2(3x+4)=3x+2[3(x-1)+2] | | 1*2=2 | | 5*(x+19)= | | 2(3x+4)=3x+2[3x-10+2] |